BRIDGING DISTANCES, ENHANCING CARE: THE TELEHEALTH REVOLUTION IN OBG NURSING - Gisha Jose, (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
Telehealth is revolutionizing the field of healthcare, and obstetric and gynecological (OBG) nursing is no exception. This research article explores the growing role of telehealth in OBG nursing, highlighting its benefits, challenges, and implications for both patients and healthcare providers. We discuss the utilization of telehealth in prenatal care, postpartum support, gynecological consultations, and education for patients and nurses. By examining current research and practical examples, the researcher aims to shed light on the transformative potential of telehealth in OBG nursing.